Differences in plasma Anti Müllerian hormone levels and reproductive parameters between two bovine species: Bos indicus and Bubalus bubalis - Berdugo, Jesús A. (Array, 2020)
The aim of this study was to evaluate the possible relationships between reproductive parameters and Anti Mullerian Hormone (AMH) levels in two closely related bovine species. AMH levels and the reproductive parameters of 50 water buffaloes (Bubalus bubalis) and 50 Zebu cattle (Bos indicus) of the same age and raised in similar conditions were evaluated. Clinical data were obtained from the farm in specialized designed format, and AMH was measured by ELISA. The results show that Zebu cattle had higher AMH levels than water buffaloes (P<0.0001), while water buffaloes exhibited better reproductive parameters: days open to pregnancy (P<0.0001), parity (P<0.0005), age at first calving (P<0.0001), and intercalving period (P<0.0001). Although both species have different reproductive parameters, no correlations were found between AMH and the reproductive parameters evaluated in either species. Finally, pregnant Zebu cattle and water buffalo showed a tendency to have lower AMH levels than non-pregnant counterparts. The results are paradoxical as the species with lower AMH levels exhibited better reproductive parameters, suggesting that the reproductive parameters within the herd do not depend solely on the ovarian reserve of females.